Perspektif Program Merdeka Belajar-Kampus Merdeka dalam Pandangan Aliran Filsafat Pendidikan Kontruktivisme dan Humanisme - Irnin Agustina Dwi Astuti; Suyitno Muslim (LITERATUS, 2022)
Philosophy has long been a source of inspiration for educational thought and practice. The Merdeka Belajar-Kampus Merdeka Policy is one of the results of thoughts and inspiration in educational practice. The concept of Merdeka Belajar-Kampus Merdeka aims to release the shackles so that it can move more easily and have autonomy to organize itself. The purpose of this study is to examine the views of educational philosophy on the concept of Merdeka Belajar-Kampus Merdeka. This research is a literature study using books and articles as study material to analyze several philosophical views on the concept of Merdeka Belajar-Kampus Merdeka. The results of the study of this article produce study materials on philosophical perspectives based on ontological bases, epistemology, axiology and according to the perspectives of the schools of p, Constructivism and Humanism to the concept of Merdeka Belajar-Kampus Merdeka.